HUBUNGAN ANTARA PANTENSI FORAMEN OVALE DENGAN KEJADIAN DECOMPRESSION SICKNESS - Rizkia, Ananda; Widyantari, Donna Diva; Shofiyanti, Nabila Indah; Putri, Ni Pt Wr Pradnya Nirmala; Syamsun, Arfi (Essential: Essence of Scientific Medical Journal, 2023)
Background: Decompression sickness (DCS) is a condition where bubbles form in the blood from dissolved gasses (usually nitrogen) which cause tissue and blood vessel injury due to a decrease in environmental pressure. One of the factors that can increase the incidence of DCS is the presence of patent foramen ovale (PFO) in divers. Method : This literature review is a study systematic review , the type used is the original article obtained through the database PubMed and ProQuest.  We use the keywords "decompression sickness," "divers with a patent foramen ovale," "divers without patent foramen ovale," and "risk" to find the articles. After tracing, a total of 303 articles were obtained and then sorted by taking into account the exclusion and inclusion criteria so that the final number obtained was two articles. Results: : This systematic review, reviewed two studies with a total of 48 subjects. Patent foramen ovale (PFO) significantly related to the risk of occurrence of events decompression sickness (DCS). PFO closure reduces the risk of DCS events associated with PFO so that divers with PFO who have experienced DCS and undergo PFO closure, do not need to stop diving after intervention. Conclusion : Divers with closed PFOs or closed shunts have a reduced risk of experiencing DCS. In these divers DCS is largely non-recurring, so they can return to dives indefinitely.